La complessità morfologica: ricerca e didattica - Pallotti, Gabriele (Incontri. Rivista europea di studi italiani, 2018)
Morphological complexity Research and teaching perspectives The article discusses a new construct and its operationalization, morphological complexity (MC). After reviewing the current literature on complexity in linguistic typology and second language acquisition research, MC is theoretically defined in terms of the range and variety of morphological processes (also called exponents) instantiated in a given text. This theoretical definition is then operationalized with a procedure (freely available online) which first identifies exponents as morphological operations on a lexical base, and then calculates the average diversity within and across samples of 10 exponents. At present, MC is calculated on verb inflections only. A first study shows that MC varies in different texts and different languages (Italian, German and English). In a second study, MC is calculated in learners of L2 Italian, and is shown to be positively correlated to general linguistic competence, as measured with a C-test, and lexical and syntactic complexity. Finally, a number of possible practical uses of the construct in a language classroom are suggested. These include the formative evaluation of learners’ morphological repertoires, and awareness-raising activities that stimulate learners to reflect on Italian’s verbal morphology, its structure, history, and theoretical description.